1 kHz, 12 MW, 300 ps microchip oscillator power amplifier system. (1st October 2022) - Zhu, Wentao; Yu, Jun; He, Huijun; Lin, Qingdian; Guo, Xiaoyang; Zhou, Cangtao; Ruan, Shuangchen
Abstract: We report a diode-pumped passively Q-switched (PQS) sub-nanosecond master oscillator power amplifier system. The master oscillator is a PQS Nd:YAG/Cr:YAG monolithic microchip laser, yielding a pulse duration of ∼300 ps and pulse energy of 33 μ J at repetition frequency of 1 kHz. After passing two stages end pumped Nd:YVO4 amplifier, the pulse energy is boosted to 3.6 mJ and pulse peak power up to 12 MW with excellent stability (root mean square ∼ 0.14%) and high beam quality ( M 2 < 1.22).